Effects of Sun-Drying on Seed Physiology of Phaseolus vulgaris L. - Simón-Figueredo, Yarlenis (2025)
Introduction. Quality seed production is a limiting factor for bean cultivation in developing countries. Objective. To evaluate the effects of sun-drying at different exposure periods on the viability and vigor of bean seeds cv. ‘Cuba Cueto 25-9N’. Materials and methods. The study was conducted at the University of Artemisa, Cuba, from January to May 2024. Freshly harvested bean seeds cv. ‘Cuba Cueto 25-9N’ were sun-dried on jute sacks under three drying durations (24, 48, and 72 h) post-treatment seed moisture content and germination were evaluated as viability criteria. Vigor assessment included germination dynamics, emergence rate, electrical conductivity, and accelerated aging test. Data were analyzed using analysis of variance and means were compared using the Tukey’s test (p ≤ 0.05). Results. The 24 and 48 h drying treatments reduced seed moisture to levels that maintained both viability (92.66 and 84.33 % germination, respectively) or vigor. The 72 h drying treatment decreased moisture to 2.96 %, negativelyaffecting viability and vigor. Conclusions. Sun-drying of bean seeds for 24 and 48 h effectively reduced moisturewhile maintaining viability and vigor, contributing to the preservation of their physiological quality under resourcelimitedconditions. The 24 h treatment proved most efficient.